Factors Affecting Toxic Friendship Communication In WorkOrganizations In Palembang City - Pebriana, Rina; Astrid, Gita; Indasari, Fera (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
The work environment is a second home for people who have jobs. Communication behavior in friendship is important in building a good social relationship. However, not all friendships can have a positive impact, on the other hand, they can also have a negative impact, such as the term toxic friendship (bad/toxic friendship) in the work environment. This research aims to determine the factors that influence toxic friendship communication in work-organizational life in Palembang City. The theory used in this research is social identity theory. The research method uses quantitative with a total of 50 respondents. The data uses questionnaire data collection techniques via Google Forms. The research results show that if it is known that the KMO MSA value is 0.500 < 0.50 and the Bartlett's Test of Sphericity (Sig.) value is 0.000 < 0.05, then the factor analysis can be continued because it meets the first requirement. The MSA value of all variables studied is > 0.50, so the second requirement in this factor analysis is fulfilled. The extraction value for all variables is >0.50. Thus it can be concluded that all variables can be used to explain factors. The variance explained table and Screen Plot show that 4 component points have an eigenvalue >1, so it can be interpreted that 4 factors are formed in toxic friendship communication that occurs in the work environment in Palembang City. The research results show that friendship dynamics can reveal the emergence of toxic friendships with unhealthy patterns. Friendships in a toxic work environment in the city of Palembang can be characterized by a lack of boundaries in communication, conflicts that are not resolved properly at work, and the emergence of passive aggressiveness at work, or even emotional manipulation